Plastic waste and microplastic issues in Southeast Asia - Ng, Chi Huey; Mistoh, Mohd Aizzan; Teo, Siow Hwa; Galassi, Andrea; Ibrahim, Azreen; Sipaut, Coswald Stephen; Foo, Jurry; Seay, Jeffrey; Taufiq Yap, Yun Hin; Janaun, Jidon (Frontiers Research Foundation, 2023)
Plastic pollution on land and in oceans is currently a pressing environmental issue. The accumulation of waste has caused severe, irreversible impacts and consequences on marine life, ecosystems, and the environment due to the lack of good waste collection, treatment, and management systems. Limited resources and infrastructure constantly challenge waste management in Southeast Asia. Therefore, we will examine the current plastic situation and issues in Southeast Asia and gain an understanding of the issues of the existing waste management systems in those countries. Then, we will examine the current practices applied in tackling plastic pollution and review the collective commitment and actions of governments, private sectors, social organizations, stakeholders, and consumers, as the key players in ending plastic pollution.